Search for large extra dimensions via single photon plus missing energy final states at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; da Silva, W. L. Prado; et al. (Amer Physical Soc, 2008)
We report on a search for large extra dimensions in a data sample of approximately 1 fb(-1) of p (p) over bar collisions at root s=1.96 TeV. We investigate Kaluza-Klein graviton production with a photon and missing transverse energy in the final state. At the 95% C.L. we set limits on the fundamental mass scale M(D) from 884 to 778 GeV for two to eight extra dimensions.